Does exposure to opioid substitution treatment at prison release reduce the risk of death? A prospective, observational study in England. (November 2016) - Marsden, John; Stillwell, Garry; Jones, Hayley; Cooper, Alisha; Eastwood, Brian; Farrell, Michael; Lowden, Tim; Maddalena, Nino; Metcalf, Chris; Shaw, Jenny; Hickman, Matthew
Abstract: Background: Opioid use disorders are common in the prison population. Prisoners face an acute risk of death in the first 4 weeks after release. We tested whether prison-based opioid substitution treatment (OST) reduces post-release mortality. Methods: This was a national prospective cohort study of adult prisoners with opioid use disorders recruited from 39 prisons (and transferred to and released from 123 prisons) in England during 2010–16 linked to Prison Health, Justice Statistics Analytical Services, Office for National Statistics, and National Drug Treatment Monitoring System. We assessed the association between OST exposure at prison release and all-cause mortality using Cox proportional hazards models adjusted for demographic and behavioural confounders and community treatment. Findings: We created a risk set of 15 141 incarcerations (12 260 individuals) with opioid use disorders (8645 exposed to OST on release, 6496 unexposed). 401 individuals died during the observation period (160 in the first year, 24 in the first month). The mortality risk in the OST-exposed group was lower than in the unexposed group in the first 4 weeks (0·93 per 100 person-years [95% CI 0·4–2·1] vs 3·67 [2·3–5·8]; unadjusted hazard ratio [HR] 0·25, 95% CI 0·10–0·64). Mortality risk did not differ from 4 weeks to 4 months (HR 1·07, 95% CI 0·57–2·00) or from 4 months to 1 year (0·97, 0·65–1·45). OST-exposed prisoners were more likely than the non-exposed group to enter community treatment (odds ratio 2·47, 95% CI 2·3–2·65). The protective effect of OST exposure was not attenuated after adjustment for demographic or behavioural confounders or for community drug treatment (adjusted HR 0·27, 95% CI 0·11–0·71). There was no evidence of an interaction between OST exposure on prison release and community treatment (ratio of HRs 0·99, 95% CI 0·12–8·11; p for likelihood ratio test=0·99). Interpretation: OST at prison release lowered risk of mortality in the first month by 75% (removing the excess risk of death in people with an opioid use disorder leaving prison compared with risk of death in the community after 4 weeks) and increased the likelihood of entering drug treatment in the community. Funding: Department of Health, NHS England, Public Health England.